Characterization of Contrast-Enhancing and Non-contrast-enhancing Multiple Sclerosis Lesions Using Susceptibility-Weighted Imaging - Eisele, Philipp; Fischer, Katja; Szabo, Kristina; Platten, Michael; Gass, Achim (Frontiers in Neurology, 2019)
Susceptibility weighted MRI (SWI) offers additional information to conventional magnetic resonance imaging (MRI) contrasts. Central veins can be identified within lesions and recently it has been suggested, that multiple sclerosis (MS) lesions with slowly expanding demyelination, so-called smoldering lesions, can be identified by a phase rim surrounding the lesion. We analyzed post contrast susceptibility weighted magnetic resonance imaging (SWI) in regard to intrinsic lesion characteristics in a cohort of MS patients. A total of 294 MS patients were evaluated using a 3 Tesla MRI. A comprehensive MRI protocol was used including post-contrast SWI. Lesions of at least 5 mm in size were analyzed on conventional MRI and SWI with a structured reporting scheme with a focus on SWI lesion characteristics. A total of 1323 lesions were analyzed: 1246/1323 (94%) were non-enhancing, 77/1323 (6%) were contrast-enhancing (CE) lesions. In CE lesions the following patterns were seen: contrast enhancement was nodular in 34/77, ring-shaped enhancement was present in 33/77 , and in 10/77 lesions areas of peripheral enhancement were present. In CEL an association with central veins was found in 38/77 (50%) lesions. In 75/1246 (6%) non-enhancing lesions a central dark dot in keeping with a central vein was seen, while 162/1246 (13%) showed peripheral hypointense dots/rims, 199/1246 (16%) showed scattered hypointense dots mainly within the lesion area, in 374/1246 (30%) no SWI hypointensity were detected. Furthermore 436/1246 (35%) lesions showed isointensity to the surrounding tissue and were not visible on SWI. SWI is able to offer additional aspects of MS pathology also when used after the application of a contrast agent. Veins connected to lesions, a potentially useful marker in the differential diagnosis of MS were seen in about 50 % of enhancing lesions. Susceptibility artifacts as they have been suggested to mark the presence of myelin-laden macrophages and smoldering inflammation were visible in 28% of lesions as hypointense dots in and in the periphery of the lesion. Given those results SWI may provide practically useful additional information in the evaluation of the lesion status in MS patients.